The Determinants of Biodiesel Price in Indonesia - Junejo, Safiullah; Wibert Victor Hasundungan, Herbert; Wicaksono, Teguh Yudo (Faculty of Economic and Business, 2025)
Research Originality: Indonesia is one of the leading producers of biodiesel globally. Despite this progress, the country surprisingly still experiences significant volatility in biodiesel prices. This phenomenon raises a critical question about the factors driving these fluctuations, which the existing literature still does not address adequately.Research Objectives: This study delves into the dynamic relationships between biodiesel prices and various potential determinants.Research Methods: The Vector Autoregressive model was employed, given its robustness in capturing dynamic interdependencies between multiple time series. The analysis utilized monthly data spanning Jan. 2016 to Dec. 2022 collected from the Ministry of Energy and Mineral Resources, Indonesia.Empirical Results: The VAR analysis reveals the nuanced influences of these variables on biodiesel prices. It suggests that an increase in the prices of CPO, crude glycerine, catalyst, and PFAD positively affects biodiesel prices, while price shocks in gasoil and methanol inversely impact them.Implications: The findings highlight the necessity for a multi-factor approach to formulating pricing strategies. They inform policy decisions to foster price stability and drive the growth of the biodiesel sector.JEL Classification: Q2, Q3, Q4, P28How to Cite:Junejo, S., Wibert, J., Hasundungan, V., & Wicaksono, T. Y. (2025). The Determinants of Biodiesel Price in Indonesia. Etikonomi, 24(1), 155 – 174. https://doi.org/10.15408/etk.v24i1.37581.